PELATIHAN MODEL ESTETIKA TAUHID DALAM BINGKAI ARSITEKTUR ISLAM DI MADRASAH ALIYAH ISLAMIC CENTRE, BIN BAZ JOGJAKARTA - Muhammad Hariyadi; Sri Redjeki; Nurbaiti Nurbaiti; Sunarto Sunarto; Mulyani Mulyani; Choliliyah Toha (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Architecture is a building art that is universal. A design architecture is part of science, art culture and civilization that cannot independent and free, instead it is influenced by yhe ideology, politics, economy ang culter of society which influence the final product of an arsitectural design. The monotheistic aesthetic in the framework of Islamic architecture describes the conceptual relationship between God, humans and nature which is a combination that cannot be separated from one another. Where Allah SWT created humans by giving them ability to reason so that they have the power to think to form a divine concept in translating the sentences of the Al-Qur’an into architectural masterpieces in the world. So that an architect can convery his spiritual messages in an architectural medium. This writing methode using Library Research with approach deskriptif kualitatif, where writing data comes from a variety of literature both in the form of text studies an relevant books. This paper attempts to describe the aesthetics of monotheism in Islamic architecture which can convery the spiritual values of an architectural work so that reflects the reality of harmony of an aesthetic of creation and science